2014
DOI: 10.1016/j.jce.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Educational qualifications mismatch in Europe. Is it demand or supply driven?

Abstract: Most papers dealing with individual overeducation risks focus on labour supply characteristics and workers behaviour. On the other hand, only few studies consider labour demand characteristics and technological change. In this paper we analyse the influence of both demand and supply factors on educational mismatch in a set of ten European countries. Our hypothesis, confirmed by results obtained using ordered probit model with sample selection, is that demand factors generally play major role in reducing educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 45 publications
1
35
1
5
Order By: Relevance
“…The results very clearly support the view that overeducation is predominantly driven by an excess in the supply of educated labour with the ratio between the number of graduates in employment and the share of workers in professional occupations highly significant in both equations. This is consistent with job competition and assignment approaches and with previous empirical findings (Verhaest and van der Velden, 2013;Ghignoni et al, 2014). However, the marginal effects are small with the models suggesting that a 10 % increase in this ratio will drive male and female overeducation rates up by 0.5 and 0.7 parentage points respectively.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The results very clearly support the view that overeducation is predominantly driven by an excess in the supply of educated labour with the ratio between the number of graduates in employment and the share of workers in professional occupations highly significant in both equations. This is consistent with job competition and assignment approaches and with previous empirical findings (Verhaest and van der Velden, 2013;Ghignoni et al, 2014). However, the marginal effects are small with the models suggesting that a 10 % increase in this ratio will drive male and female overeducation rates up by 0.5 and 0.7 parentage points respectively.…”
Section: Resultssupporting
confidence: 90%
“…Croce and Ghignoni (2012), in their pooled model for 26 European countries, found that the ratio of wages of graduates to those of less-qualified workers is associated with graduate overeducation and also that recession leads to overeducation, with graduates accepting jobs requiring less education than they possess. Ghignoni and Verashchagina (2014) explore determinants of individual overeducation risk in 10 European countries taking into account both supply -side and demand -side factors. This paper provides further evidence on the issue, with an assessment of the determinants of international variations in overeducation rates using European data and, in addition to structural factors, assesses the potential contribution of labour market uncertainty, labour market institutions, education funding mechanisms and migration as determining factors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual characteristics may be more important than macro-level factors (Ghignoni and Verashchagina 2014). At the microeconomic level, five categories of factors have been found to affect the risk of overeducation: (1) ability, academic performance, and personality; (2) gender and age; (3) immigrant background; (4) labour market and job characteristics; and (5) characteristics of education.…”
Section: Determinants Of Job Polarization and Skills Mismatchmentioning
confidence: 99%